ROLE OF KERALA FINANCE CORPORATION (KSFE) IN MAKING SAVINGS HABIT AMONG ITS CUSTOMERS THROUGH THE CHIT FUNDS - N. K. BABU (International Journal of Psychosocial Rehabilitation, 2020)
Chit fund is a mixture of a loan and a recurring deposit. The KSFE is a Functional Non-trading Financing Corporation, is wholly owned by the Government of Kerala. It is one of the States most profitable public sector enterprises. The Government of Kerala framed with both the purpose of achieving the private chit promoters with an alternative to the public to introduce social control over. The KSFE has provided the consumers with many more schemes, which are very helpful. They will offer hands-on price money, and it brings our full money securities. The KSFE returns to the customer’s perspective very helpful and also established provisions for gold loans. The present study aims to analysis on savings habits among KSFE’s customers, especially chit funds